Characterisation and physiochemical properties of mango peel pectin extracted by conventional and phase control microwave-assisted extractions - Sriwattana, S. (2021)
Natural pectins from fruit peel have applications in the food industry as food stabilisers, sources of dietary fiber and as bio-waste. Here, we investigated the physicochemical properties of mango-peel pectin, after using conventional extraction and phase control microwaveassisted extraction (PCMAE). Due to its effectiveness as a bio-waste, a high peel-to-fruit weight ratio and fiber content, we used the Sam-pee mango cultivar from Northern Thailand for this study. The highest pectin yield found was 10.45% (w/w) after using PCMAE at 500W. The characterisation of extracted pectin revealed that the equivalent weight was higher when pectin was extracted using PCMAE, while the methoxyl content was lower and the degree of esterification remained constant (~55%). The PCMAE at 500W provided an emulsion activity pattern similar to that of the conventional extraction method. Phytochemical properties of the pectin however, measured by total phenolic content and antioxidant scavenging activities, were not significantly different (p < 0.05) between PCMAE and conventional methods. At a higher microwave radiation during the PCMAE (900W), the levels of antioxidants measured in the mango-peel pectins declined.